Application of the Internet of Things (IoT) in Health: the Future of Personal Care - Chevi Herli Sumerli A; Noor Diah Erlinawati; Dito Anurogo; Dadang Muhammad Hasyim; Abdullah Ardi (Yayasan Adra Karima Hubbi, 2024)
The application of the Internet of Things (IoT) in healthcare has revolutionized healthcare in an unprecedented way. IoT allows devices to interconnect, collect data, and exchange information in real-time, which can improve health monitoring, diagnosis, and disease management in a more effective way. This research aims to investigate the potential application of the Internet of Things (IoT) in improving personalized healthcare. The focus is on the ability of IoT to monitor health conditions in real-time, improve early diagnosis, provide customized care, and increase the overall efficiency of the health system. This research uses a qualitative and quantitative approach by conducting a literature review on the application of IoT in healthcare, as well as analyzing data from case studies of IoT technology implementation in personal healthcare. The results of this study reveal the great potential of IoT applications in improving personal healthcare, including remote monitoring of patient conditions, data-driven disease prediction, individualized treatment customization, and cost efficiency in the healthcare system. The implementation of IoT technology also brings challenges such as data privacy, system security, and cross-platform integration that need to be overcome to maximize its benefits. The conclusion of this study is that the application of the Internet of Things (IoT) in healthcare promises a more effective and efficient future of personalized healthcare. However, technical, ethical, and security challenges need to be overcome for these applications to be successful. With an increased understanding of the benefits and risks of IoT adoption in healthcare, appropriate steps can be taken to ensure better personalized healthcare in the future.